Fisheries and the Law in Europe Regulation After Brexit - Echebarria Fernández, Jonatan; Johansson, Tafsir Matin; Skinner, Jon A.; Lennan, Mitchell (Legal Perspectives on Brexit, 2022)
Examining fisheries, Brexit, the Trade and Cooperation Agreement (TCA) and its consequences for the Fishing Industry in the UK and the EU, this book explores key issues within the complex topic of fisheries after Brexit. Assessing the new fishing relationship between the UK and the EU, which will continue to develop over the next decade, it provides an important study of the state of fisheries post-Brexit. Taking a cross-cutting economic, legal and policy approach, the book outlines the social and economic impacts of Brexit on the UK and EU fishing industries. It critically analyses the provisions relevant to fisheries in the TCA, reflects on the bilateral fishing negotiations between the EU, UK and Norway, providing inferences as to what the "new and special relationship" might be in fisheries. It then focuses on the 2020 Fisheries Act and explores internal divergences in the nations of the UK because of devolution. Taking an international approach, the work offers an exploration of cooperation in fisheries enforcement, international and regional obligations in marine conservation, and the new horizons for the UK in international fisheries organizations and arrangements now it is no longer a member of the EU. It offers an overview of expert opinion on fisheries post-Brexit, highlighting lessons learned and future developments for fisheries in a post-Brexit world. Having finally signed the Trade and Cooperation Agreement on 31 December 2020 after tense negotiations, the United Kingdom and European Union have found themselves in a new fisheries relationship. This book maps the complex social, economic, legal and policy issues of fisheries in a post-Brexit world and will be of interest to stakeholders and scholars.